Sodobni pristopi inženiringa poslovnih sistemov - Maletič, Matjaž; Urh, Benjamin (2022)
Modern Approaches to Enterprise System Engineering. Modern approaches to enterprise system engineering are an important factor in maintaining or creating competitive advantage for an organization. It is important that both management and employees of the organization are aware of the concepts of each approach. In this monograph, we present modern approaches that deal with the operation of the organization from various aspects of its competitiveness, and to which we have perhaps paid too little attention so far. Digitization of the project environment, new perspectives on product development, asset management, efficiency and effectiveness of business processes, the use of modern information and communication technologies and their impact on the design and operation of the organization, and ensuring appropriate working conditions and a working environment for the safety and health of employees are approaches that organizations will have to win in the future if they want to remain competitive. In addition to theoretical presentations on the establishment and application of the individual approaches, individual examples from practice are also presented.
Keywords: management; business systems; efficiency and effectiveness; engineering approaches; digital transformation; development; work environment